SOAL KEMAMPUAN PEMECAHAN MASALAH MATEMATIS BERKONTEKS KEARIFAN LOKAL BENGKULU - Marizka Purnamayana; Nyayu Masyita Ariani (JURNAL PENDIDIKAN MATEMATIKA UNIVERSITAS LAMPUNG, 2021)
AbstractThis study aims to produce products in the form of mathematical problem-solving ability questions based on Bengkulu local wisdom that are valid, clear, and have a good level of difficulty and discriminatory index. The subjects in this study were 30 grade VIII students of SMPN 07 Bengkulu Selatan. This development research was conducted using the Tessmer model which consisted of preliminary, self-evaluation, expert review, one-to-one, and small group stages. The data analysis used was qualitative analysis at the expert review stage to determine the validation of the questions, both in terms of content, construction, and language; one-to-one process analysis to find out the clarity of the questions, and quantitative analysis of the results of the small group to determine the characteristics of good questions based on the level of difficulty and the index of discriminating power of the questions. Based on the results of data analysis, this study produced 7 standardized questions from 10 questions that had gone through the expert review, one-to-one, and small group stages. Standardization can be seen from the level of difficulty and a good item discriminatory index.Keywords: bengkulu local wisdom; mathematical problem solving; questionsDOI: http://dx.doi.org/10.23960/mtk/v9i4.pp467-481